Degree of conversion of micro-hybrid, nano-hybrid and Ormocer composites using LED and QTH light-curing units - Seied Mostafa Fatemi; Akbar Fazel Najafabadi; Mohammad Erfan; Tahereh Sadat Jafarzadeh Kashi; Marjan Behroozibakhsh; Haleh Hali; Hosein Bagheri Gorgani (Tehran University of Medical Sciences, 2012)
Background and Aims: The aim of this study was to measure the degree of conversion (DC) of three types of composite resins (micro-hybrid, nano-hybrid and Ormocer) with different light curing units (LED LCU and QTH LCU) in two depths.Materials and Methods: Three commercially available dental resin composites were used in this study: (Tetric Ceram, Ivoclar Vivadent, Liechtenstein-A2 shade), (Tetric Evoceram, Ivoclar Vivadent, Liechtenstein-A2 shade), (Ceram X, Dentsply, Germany-M2 shade). Specimens were divided into two groups, 5 specimens were photo-activated by QTH unit (Coltolux 75-Colten) and the other five specimens were cured by LED (Demi-Kerr). Then each specimen was sectioned at the top surface and at 2-mm depth. The DC was measured by FT-IR(Bruker-tensor 27). The data were analyzed by 3-way ANOVA test.Results: There was significant difference between tested composite resins (P<0.001). The results of top surfaces were significantly different from those observed at 2-mm depth (P<0.001). The type of curing unit affected the polymerization of Ceram X resin composite.Conclusion: This study showed a significant difference in the degree of conversion in different thicknesses within three groups of resin composites.